A synthesic of evolutionary theory - Ross, Herbert Holdsworth (Prentice-Hall, 1962)
This is book introduction the expansion of evolutionary conceps, the evolution of the univers, life: its nature and origin, the source of variability, natural selection, spwcies and speacies change, increase in the number of species, the evolution of communities...